Fates of nutrient elements and heavy metals during thermal conversion of cattle slurry-derived anaerobic digestates - Daniel J. Lane; Olli Sippula; Jorma Jokiniemi; Mikko Heimonen; Niko M. Kinnunen; Perttu Virkajärvi; Narasinha Shurpali (Bioresources and Bioprocessing)
Abstract Thermal processes are emerging as promising solutions to recovering phosphorus and other nutrient elements from anaerobic digestates. The feasibility of nutrient element recovery depends largely on the fates of nutrient elements and heavy metals during thermal processing. This study assesses the partitioning of macronutrients (N, P, K, Na, Ca and Mg) and heavy metals (Zn, Cu, and Mn) between condensed and gaseous phases during thermal conversion of cattle slurry digestates in gas atmospheres of pyrolysis, combustion, and gasification processes. This study also assesses the chemical forms of macronutrients retained in combustion ashes. The partitioning of elements between condensed and gaseous phases was quantified by mass balances based on elemental analyses of char and ash residues. The char and ash residues were prepared in a fixed-bed, batch reactor at temperatures within the range 800–1000 °C. Powder X-ray diffraction was used to identify the chemical forms of macronutrient elements in combustion ashes. Volatilisation of P was low (< 20%) when the digestates were heated in inert and oxidising atmospheres, whereas a reducing atmosphere volatilized P to a major extent (~ 60% at 1000 °C). Oxidising atmospheres increased volatilisation of N but suppressed volatilisation of K, Na, and Zn. Volatilisation of the following elements was low (< 30%) in all investigated operating conditions: Ca, Mg, Mn, and Cu. The combustion ashes contained both high concentrations of P (around 7 w/w%) and acceptable concentrations of regulated heavy metals (Cu, and Zn) for application on agricultural and forest soils in Finland. Phosphorous was retained in the combustion ashes in the form of whitlockite. This form of P is expected to be available to plants when the ashes are added to soil.